Pengaruh minyak zippo pada kecepatan rambatan api dan residu dari komposit epoksi dengan penguat serat jute - N.M.A.R. Adriani; I.G.K Sukadana; I.G.A.K.C. Adhi; I.D.G.A. Subagia (Universitas Mataram, 2021)
This study investigated the rate of flame propagation and residue quality of epoxy composite with jute fiber reinforcement. Three layer of jute fibers were stacked as reinforcement of composites. It was manufactured by the injection method (vacuum assisted injection, VARI). In this study, the zippo oil as flame trigger was added on the specimen. This study aims to investigate the effects of zippo oil on the rate of flame propagation and residue of composites. The flame rate testing was based on ASTM D 635 standard, with repetitions of 5 times for each sample that conducted inside of the combustion chamber. Test results obtained in addition to carbon dioxide (CO2) are carbon monoxide (CO) and methane (CH4), as well as dust particles (PM10). The result of measuring the flame propagation rate with zippo fuel is 0.23 mm/s, while composite without zippo oil is 0.17 mm/s. Furthermore, CO2 residue with zippo oil addition is 1.55% and without zippo oil is 1.57%, respectively. Meanwhile, residual test results for contaminants such as carbon monoxide (CO) and Methane (CH4) from composites with the addition of zippo oil were 0.006 % and 0.008% respectively. In additional, the remaining composite burned without zippo oil has an equal value of CO and methane about 0.002%. The conclusion shows that there was an increase of flame propagation rate and residual value produced after the addition of zippo oil, and that pollutant residues exceeded threshold value.